2021
DOI: 10.3390/healthcare9080962
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stigma as a Contextual Barrier to Early Uptake of HIV Testing, Treatment Initiation, and Disclosure; the Case of Patients Admitted with AIDS-Related Illness in a Rural Hospital in South Africa

Abstract: We explored the extent to which perceived HIV-related stigma influences the disclosure and concealment of HIV status to family among adult patients hospitalised for AIDS-related illness, and described reports of negative responses and enacted stigma following disclosure. We conducted interviews with a purposeful sample of 28 adult patients in a rural South African hospital. Data analysis was deductive and inductive and followed the thematic approach. We found evidence of delayed HIV diagnosis and initiation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…The findings of this study showed that some participants disclosed their HIV status to a select few confidants, one or two family members due to fear of stigma and discrimination. These findings concur with those of a study conducted in South Africa by Madiba, Ralebona, and Lowane ( 2021 ), who posit that disclosure to family and friends about one’s HIV status is usually deliberate, selective, and often planned, where PLWHIV tend to weigh the risks and benefits associated this planned disclosure. Related to this, study findings by Antonini et al ( 2021 ) emphasise the importance of professional counselling and psycho-social support in assisting couples to cope with HIV-discordance and related disclosure.…”
Section: Discussionsupporting
confidence: 89%
“…The findings of this study showed that some participants disclosed their HIV status to a select few confidants, one or two family members due to fear of stigma and discrimination. These findings concur with those of a study conducted in South Africa by Madiba, Ralebona, and Lowane ( 2021 ), who posit that disclosure to family and friends about one’s HIV status is usually deliberate, selective, and often planned, where PLWHIV tend to weigh the risks and benefits associated this planned disclosure. Related to this, study findings by Antonini et al ( 2021 ) emphasise the importance of professional counselling and psycho-social support in assisting couples to cope with HIV-discordance and related disclosure.…”
Section: Discussionsupporting
confidence: 89%
“…Whilst decentralization of services provides easier access to services, new modalities of HIV testing including self -testing [ 24 ] may have not reached saturation in some communities. Furthermore, many individuals in these communities face structural and individual level barriers that decrease access to both information about services and to the services themselves, and may also include fear of stigma and discrimination, all of which pose major obstacles to HIV testing [ 34 36 ]. Many individuals may also be unaware of the benefits and services to which they are entitled to and often lack skills required to engage with authorities around services.…”
Section: Discussionmentioning
confidence: 99%
“…It was also noted that participants who reported rejection were those who disclosed their HIV status to their family members (Evangeli & Wroe 2017 ; Madiba, Ralebona & Lowane 2021 ). A study conducted in China about families’ reactions and responses towards HIV among the infected members revealed that most family members were less concerned about the health and feelings of their HIV-positive relatives (Yu et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%